THE ROLE OF ARTIFICIAL INTELLIGENCE IN IMPROVING TRANSPARENCY AND ACCOUNTABILITY OF SHARIA PRODUCT MARKETING - Marsono, Adi; Fitrotus Sa'diyah, Dewi; Moh. Agil Nuruzzaman; Farid Nur Jayanto (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
This study examines the role of Artificial Intelligence (AI) in enhancing transparency and accountability in the marketing of Sharia-compliant products. In the digital era, adhering to Sharia principles in product marketing is essential for maintaining consumer trust. AI plays a pivotal role in automating data analysis, supply chain tracking, and halal compliance verification, ensuring that the information provided to consumers is accurate and transparent. Additionally, AI enables early detection of inconsistencies or deviations in marketing processes, bolstering the accountability of Sharia-based institutions. This research aims to provide insights into how AI integration can reinforce Islamic ethical values, improve operational efficiency, and build market trust in Sharia-compliant products.